ANALISIS KLT BIOAUTOGRAFI EKSTRAK KULIT BATANG TANAMAN KAYU JAWA (Lannea coromandelica) TERHADAP BAKTERI Staphylococcus aureus DAN Shigella dysentriae - yumita yumita; Abdul Rahman Razak; Indriani; Syaiful Bahri (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2019)
Java wood plants (Lannea coromandelica) is a traditional medicinal plant which is still often used by people to treat internal and external wounds. The study aims to determine the effect of solvent polarity in Javanese stem bark extract on Staphylococcus aureus and Shigella dysenteriae, and to identify the compound groups which had an antibacterial activity against Staphylococcus aureus and Shigella dysenteriae with KLT-Bioautography analysis. The results show that the n-hexane extract of Javanese bark is not showing an antibacterial activity against Staphylococcus aureus and Shigella dysenteriae, whereas the ethyl acetate extract and methanol of Javanese bark show an antibacterial activity against Staphylococcus aureus and Shigella dysenteriae. The results of the TLC-Bioautography test show negative results for Staphylococcus aureus and Shigella dysenteriae. Keywords: Lannea coromandelica, antibacterial, Staphylococcus aureus, Shigella dysentriae, KLT-Bioautografi